When spinal instrumentation revision is not an option: Salvage vertebral augmentation with polymethylmethacrylate for mechanical complications: A systematic review - Derek T. Cawley; Kiran Divani; Roozbeh Shafafy; Aiden Devitt; Sean Molloy (Brain and Spine, 2023)
Intoduction: Mechanical complications from spinal fusion including implant loosening or junctional failure result in poor outcomes, particularly in osteoporotic patients. While the use of percutaneous vertebral augmentation with polymethylmethacrylate (PMMA) has been studied for augmentation of junctional levels to offset against kyphosis and failure, its deployment around existing loose screws or in failing surrounding bone as a salvage percutaneous procedure has been described in small case series and merits review. Research Question: How effective and safe is the use of PMMA as a salvage procedure for mechanical complications in failed spinal fusion?. Materials and Methods: Systematic search of online databases for clinical studies using this technique. Results: 11 studies were identified, only consisting of two case reports and nine case series. Consistent improvements were observed in pre- to post-operative VAS and with sustained improvements at final follow-up. The extra- or para-pedicular approach was the most frequent access trajectory. Most studies cited difficulties with visibility on fluoroscopy, using navigation or oblique views as a solution for this. Discussion and Conclusions: Percutaneous cementation at a failing screw-bone interface stabilises further micromotion with reductions in back pain. This rarely used technique is manifested by a low but increasing number of reported cases. The technique warrants further evaluation and is best performed within a multidisciplinary setting at a specialist centre. Notwithstanding that underlying pathology may not be addressed, awareness of this technique may allow an effective and safe salvage solution with minimal morbidity for older sicker patients.